Nanocomposite Polymer Scaffolds Responding under External Stimuli for Drug Delivery and Tissue Engineering Applications. Issue 2 (10th December 2019) - Mertz, Damien; Harlepp, Sébastien; Goetz, Jacky; Bégin, Dominique; Schlatter, Guy; Bégin‐Colin, Sylvie; Hébraud, Anne
Abstract: The blossoming development of nanomaterials and polymer science has opened the way toward new biocompatible scaffolds responding remotely to external stimuli (magnetic field, light, electric field). Such smart scaffolds are envisioned as new implantable tissues displaying multiple therapeutic and imaging functionalities. They hold great promises to achieve a controlled delivery of therapeutics for various diseases, or to ensure a stimuli‐induced cellular response for bone, cardiac, or muscle tissue engineering. Abstract : Biocompatible nanocomposite polymer scaffolds responding remotely to external fields (magnetic, electric, light) are envisioned as new implantable materials having therapeutic and imaging functionalities. They are designed to achieve a controlled drug delivery for various diseases, or a stimuli‐induced cellular response for tissue engineering applications.